The feasibility of pancreatic duct stenting using a novel 4-Fr plastic stent with a 0.025-in. guidewire - Kazumasa Nagai (Nature Portfolio, 2021)
Abstract Pancreatic duct stenting is a well-established method for reducing post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. However, there is no consensus on the optimal type of plastic stent. This study aimed to evaluate the feasibility and safety of a new 4-Fr plastic stent for pancreatic duct stenting. Forty-nine consecutive patients who placed the 4-Fr stent into the pancreatic duct (4Fr group) were compared with 187 consecutive patients who placed a conventional 5-Fr stent (control group). The primary outcome was technical success. Complications rate, including post-ERCP pancreatitis (PEP) were the secondary outcomes. Propensity score matching was introduced to reduce selection bias. The technical success rate was 100% in the 4Fr group and 97.9% in the control group (p = 0.315). Post-ERCP amylase level was significantly lower in the 4-Fr group than the control group before propensity score matching (p = 0.006), though without statistical significance after propensity score matching (p = 0.298). The rate of PEP in the 4Fr group (6.1%) was lower than the control group (15.5%), though without statistical significance before (p = 0.088) and after (p = 1.00) propensity score matching. Pancreatic duct stenting using a novel 4-Fr plastic stent would be at least similar or more feasible and safe compared to the conventional plastic stent.